"Left-hand strategy" for the design, synthesis and discovery of novel triazole–mercaptobenzothiazole hybrid compounds as potent quorum sensing inhibitors and anti-biofilm formation of Pseudomonas aeruginosa. (11th November 2021) - Tung, Truong Thanh; Xuan, Huy Luong
Abstract : Triazole–benzothiazole hybrids as potent quorum sensing inhibitors and antibiofilm formation of Gram-negative bacteria. Abstract : Herein, a library of novel hybrid 6-(4-substituted-1 H -1, 2, 3-triazol-1-yl)-2-mercaptobenzothiazoles was designed using a "left-hand strategy" and synthesized using microwave-assisted synthesis. The synthesized compounds were screened against quorum sensing activities and biofilm formation of Gram-negative bacteria. Biological results reveal that eleven compounds strongly inhibited the quorum sensing activities of the Pseudomonas aeruginosa lasB-gfp reporter strain. Compounds 4g (IC50 of 9.84 ± 1.10 μM), 4h (IC50 of 6.09 ± 0.98 μM), and 4m (IC50 of 12.20 ± 0.25 μM) are 2–5 times stronger than the reference compound 4NPO (IC50 of 32 ± 0.88 μM) in QSI screening. Compounds 4g and 4h inhibited up to 90% of the biofilm formation of Pseudomonas aeruginosa . In terms of anti-virulence effects, compounds 4g and 4h strongly inhibited the production of violacein by Chromobacterium violaceum and protease by Pseudomonas aeruginosa .